Application of biodegradable surfactant in cold rolled steel corrosion inhibitor in membrane separation device process
By adding the biodegradable surfactant dodecyldimethylbetaine (BS-12) to the cold-rolled steel solution, the protective film is formed using its physical and chemical adsorption properties, and the cold-rolled steel is solved in the membrane separation device. The corrosion problem achieves efficient anti-corrosion performance and environmentally friendly low-cost solutions.
Patent Information
- Application Number
- CN202411249253.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-14
AI Technical Summary
Cold-rolled steel is susceptible to corrosion in membrane separation devices. The existing inhibitors have problems of environmental pollution and high dose use, making it difficult to effectively protect the surface of cold-rolled steel at low doses.
The biodegradable surfactant dodecyldimethyl betaine (BS-12) was used to add the cold-rolled steel solution within the concentration range of 0.5-15 mg·L-1, and a protective film was formed by physical and chemical adsorption. Inhibit contact between water molecules and corrosive media and improve the corrosion resistance of cold-rolled steel.
BS-12 shows good solubility and corrosion inhibition efficiency in acidic, neutral or alkaline aqueous solutions, which can significantly improve the corrosion resistance of cold-rolled steel at a lower amount, and its molecular weight is suitable for not entering the permeate to avoid The membrane separation system brings side effects, achieving a corrosion inhibition efficiency of 95.3%.
Smart Images

Figure CN119307927A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to application of a biodegradable surfactant in a cold-rolled steel corrosion inhibitor in a membrane separation device process, belonging to the technical field of membrane separation and corrosion inhibition. Background Art
[0002] Water purification, reuse and safe drinking water are becoming increasingly important worldwide. In many countries, it is very important to purify water by membrane separation process to meet the standards for reuse. Considering the membrane cost, water must be pretreated to good quality before treating the membrane device, which requires the addition of chlorine-containing disinfectants. In addition, acid-containing solutions are usually used to remove pollutants adsorbed on the membrane surface to restore membrane performance. Most membrane treatment devices are made of cold rolled steel (CRS) because of their strength, toughness and weldability, such as seawater pretreatment devices (carbon steel) and membrane separation chambers (stainless steel) of various important machines in seawater desalination plants. However, the main component in CRS is Fe, which has active chemical properties. When operating under complex conditions (acid, alkali, salt solution, etc.), CRS will inevitably be corroded. Fe in CRS will undergo redox reactions, produce electrochemical corrosion, accelerate the corrosion of CRS, threaten equipment operation, and increase enterprise costs. Therefore, improving the anti-corrosion performance of CRS has become a research hotspot in recent decades.
[0003] Researchers have tried to improve the inhibition performance of CRS by coating, electrochemical protection and adding inhibitors. Among these methods, adding inhibitors has attracted much attention due to its simple operation, low dosage and high inhibition efficiency, including inorganic, organic and polymer inhibitors. Traditional inorganic inhibitors are gradually replaced due to their high dosage and high pollution. Organic inhibitors are composed of polar (O, N, S, P) and non-polar (C, H) groups. Polar groups can be adsorbed on the surface of CRS, and non-polar groups can form a hydrophobic layer. The formation of the hydrophobic layer can inhibit the movement of H2O to the surface of CRS and protect CRS from corrosion. Importantly, organic inhibitors are widely available and have environmentally friendly properties, such as plant inhibitors and surfactants. The disadvantage of plant inhibitors is that they cannot completely cover the surface of CRS at low doses due to their limited adsorption sites. They are not suitable for the treatment of CRS at high doses (~300 mg·L -1 ) showed good corrosion inhibition effect.
[0004] The surfactant structure contains a water-soluble polar head and a water-insoluble tail, and has an amphiphilic nature. Surfactants can be adsorbed on metals and metal oxides, with the polar head moving toward the metal surface and the non-polar tail moving toward the solution, inhibiting movement toward the metal and improving the corrosion inhibition performance of the metal. Surfactants stand out for their high corrosion inhibition efficiency at relatively low doses.
[0005] Ma et al. synthesized polymer surfactants by free radical polymerization using allyl glycidyl ether, acrylamide, butyl acrylate and sodium allyl sulfonate as raw materials. The surfactants were 500 mg·L -1 The corrosion inhibition efficiency of carbon steel can reach 95%. Chen et al. selected surfactant octylphenol polyoxyethylene ether phosphate (OP-10P) and 1,10-decanedithiol (DD) as a combined anticorrosion additive for zinc-air batteries in concentrated alkaline solutions. The results showed that the combined corrosion inhibitor can effectively inhibit the self-corrosion of Zn in a dormant state, and the corrosion inhibition efficiency can reach 99.9% at the optimal ratio.
[0006] However, the abuse of surfactants can damage the environment and cause eutrophication of water bodies. Biodegradable surfactants have become a hot topic of research due to their environmental friendliness. Therefore, it is of great significance to the membrane separation industry to find a surfactant that has good inhibition efficiency for CRS and has a suitable molecular weight, and its addition does not damage membrane performance. Summary of the invention
[0007] The purpose of the present invention is to provide an application of a biodegradable surfactant in a cold-rolled steel corrosion inhibitor in a membrane separation device process, by using dodecyl dimethyl betaine as an inhibitor to improve the corrosion inhibition efficiency of CRS, and in membrane separation, it will not enter the permeate and will not bring side effects to the separation system.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The method of using a biodegradable surfactant to slow down the corrosion of cold-rolled steel is to add the biodegradable surfactant to a solution system having cold-rolled steel; wherein,
[0010] The biodegradable surfactant is dodecyl dimethyl betaine, and the concentration in the solution system is 0.5-15 mg·L -1 ;
[0011] The concentration of the corrosive medium in the solution system is 0.05-2 mol·L -1 .
[0012] Preferably, the temperature of the solution system with the cold rolled steel is 200-400K.
[0013] Preferably, the corrosive medium is trichloroacetic acid.
[0014] The application of biodegradable surfactant in cold rolled steel corrosion inhibitor in membrane separation device process is to add biodegradable surfactant to feed liquid and pass through membrane separation system with cold rolled steel;
[0015] The biodegradable surfactant is dodecyl dimethyl betaine, and its concentration in the feed liquid is 0.5-15 mg·L -1 .
[0016] Preferably, the membrane used in the membrane separation system is a negatively or positively charged membrane.
[0017] Preferably, the membrane used in the membrane separation system is a nanofiltration membrane.
[0018] Preferably, the membrane used in the membrane separation system is used to separate Na2SO4 or MgSO4 in the feed liquid.
[0019] A method for predicting the adsorption type of a surfactant on a cold-rolled steel surface, wherein the surfactant has a molecular structure including a glycine group and an alkyl group containing 8 to 16 carbon atoms connected to the nitrogen atom; the method comprises the following steps:
[0020] The radial distribution function between the surfactant and the cold-rolled steel surface was calculated by molecular dynamics simulation. If the peak appears If the value is below , it is chemical adsorption, otherwise it is physical adsorption;
[0021] Alternatively, by calculating the projected density of states before and after the surfactant is adsorbed on the Fe(110) surface, if the adsorbed N, O heteroatoms and P orbitals overlap with the Fe d orbital, and the N and O p orbital curves change, the Fe d orbital energy increases, indicating that the surfactant donated electrons to the Fe d orbital and chemical adsorption occurred.
[0022] The beneficial effects of the present invention are:
[0023] The biodegradable surfactant dodecyl dimethyl betaine (BS-12) was used as an inhibitor. It exhibits good solubility in acidic, neutral or alkaline aqueous solutions and has a polar head and a non-polar tail with a C-12 chain length, which is beneficial for inhibiting the movement of H2O molecules to the surface of CRS and improving the anticorrosion performance of CRS.
[0024] First, BS-12 is inexpensive, biodegradable, environmentally friendly, and can save corporate costs; second, the structure of BS-12 has a C-12 chain length, which is suitable for giving CRS good anti-corrosion properties at a lower addition amount; third, the molecular weight of BS-12 (271.44 g·mol -1 ) is sufficient to prevent BS-12 molecules from entering the permeate and causing side effects in the separation system.
[0025] Weight loss method and electrochemical test show that in 0.1MTCA solution, 10mg·L -1The addition of BS-12 in an amount of 100% can make CRS have good corrosion inhibition efficiency (95.3%). A series of characterizations proved that the addition of BS-12 kept the CRS surface constant. The adsorption mechanism of BS-12 was further analyzed at the molecular / atomic level using DFT, MD simulation and state density calculation. It was proved that BS-12 molecules formed a protective film in the solution / steel through physical and chemical adsorption, thereby inhibiting the corrosion of CRS in trichloroacetic acid. It can provide valuable insights into the corrosion of CRS in seawater softening membrane devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 (a) Inhibition rate and (b) corrosion rate of CRS in 0.1 MCl3CCOOH containing different concentrations of BS-12 tested under different conditions; (c) Corrosion thermodynamics and (d) kinetic parameters of CRS tested at 293 K;
[0027] Figure 2 (a) Polarization curves and (bc) EIS tests of CRS after immersion in 0.1 M trichloroacetic acid solution with different BS-12 concentrations at 293 K for 0.5 h. (d) Equivalent circuit model;
[0028] Figure 3 To make CRS contain 10mg·L at 20℃ -1 SEM surface morphology, (b) AFM and (c) CLSM tests of BS-12 after immersion in Cl3CCOOH solution for 6 h;
[0029] Figure 4 (a) ATR-FTIR spectrum, (b) CRS surface chemical analysis and (cf) CRS containing 10 mg·L at 20 °C -1 Elemental deconvolution analysis of BS-12 after immersion in 0.1MCl3CCOOH solution for 6h;
[0030] Figure 5 (a) HOMO and (b) LOMO, (c) f(r→)^+, (d) f(r→)^-, and (e) atomic Mulliken charges in the optimized structure, (e1) optimized structure, (e2) ESP diagram;
[0031] Figure 6 are (ac) equilibrium adsorption configurations of inhibitors and (df) radial separation functions (RDFs) on the Fe(110) plane;
[0032] Figure 7 Projected density of states: (a) electron exchange between the optimized structure molecule and Fe(110), (b) PDOS diagram of Fe, N, and O atoms before and after adsorption;
[0033] Figure 8 The membrane performance stability test of two typical nanofiltration membranes. (a) Negatively charged nanofiltration membrane, (b) Positively charged nanofiltration membrane;
[0034] Fig. 9 (a) Corrosion and (b) inhibition mechanisms of CRS in different corrosive solutions;
[0035] Fig.10 Six adsorption isotherms were used to evaluate the adsorption behavior of BS-12 on the CRS surface;
[0036] Fig.11 This is the EIS test of CRS in trichloroacetic acid for different immersion times;
[0037] Fig.12 This is a comparison chart of the corrosion inhibition effects of five different types of corrosion inhibitors on steel in a trichloroacetic acid environment. DETAILED DESCRIPTION
[0038] Membrane technology is an effective way to achieve resource recycling, but most membrane devices are made of cold-rolled steel plates, which are easily corroded under acidic conditions. The present invention uses a biodegradable surfactant, dodecyl dimethyl betaine (BS-12), as a corrosion inhibitor to protect CRS in trichloroacetic acid (TCA) solution. The long-term stability test of the membrane shows that the addition of BS-12 does not damage the membrane performance; the weight loss experiment proves that the addition of a trace amount (10 mg·L -1 )BS-12 can produce a good corrosion inhibition efficiency (95.3%) for CRS. Electrochemical tests show that the mixed corrosion inhibitor BS-12 has a corrosion inhibition effect on both the anode and the cathode, and the polarization resistance increases by 21 times; SEM, AFM and CLSM tests prove that the addition of BS-12 can keep the CRS surface stable. FTIR and XPS tests prove that BS-12 is adsorbed on the CRS surface through physical adsorption and chemical adsorption. Theoretical calculations prove the horizontal adsorption of BS-12 on the CRS surface and the existence of electron transfer between BS-12 and CRS. BS-12 shows great potential in the inhibition of CRS in membrane separation and purification processes.
[0039] 1 Experiment
[0040] 1.1 Materials
[0041] The CRS samples used in the corrosion test (composition: C0.07%, S0.01%, Al0.03%, Si0.01%, Mn0.3%, and the rest is Fe) were provided by Panzhihua Steel Group Co., Ltd. Trichloroacetic acid (CH3CCOOH, AR, Macklin) was designed as the corrosion medium. Amphoteric surfactant BS-12 (C 16 H 33NO2, AR) were purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd. and used to evaluate the corrosion inhibition effect of BS-12 on CRS in 0.1 mol / L CH3CCOOH solution. MgCl2 and Na2SO4 were provided by Sinopharm Chemical Reagent Co., Ltd. and used to evaluate the effect of BS-12 addition on membrane performance.
[0042] 1.2 Study of corrosion behavior by weight loss method
[0043] The CRS surface was polished to be smooth with sandpaper, and the CRS sample was cut into pieces of 20 mm × 25 mm × 0.7 mm in size. The CRS was wiped with acetone to remove surface grease, and the sample was placed in an oven to dry, and then the weight (w0) was recorded. The sample was placed in 0.1 M trichloroacetic acid for 6 hours for corrosion test, and then the surface corrosion products were cleaned with deionized water. The CRS fragments were dried and the weight (w1) was recorded. Therefore, the corrosion rate can be calculated by Formula 1:
[0044]
[0045] Where: v is the corrosion rate, S is the surface area of the CRS sample (m 2 ), t is the immersion time in 0.1MCl3CCOOH solution (h). After adding the corrosion inhibitor, the corrosion rate is suppressed, so the corrosion inhibition efficiency (η w ) can be calculated by formula 2:
[0046]
[0047] where η w is the corrosion inhibition rate, v0 is the corrosion rate of CRS in Cl3CCOOH solution, and v is the corrosion rate of CRS in Cl3CCOOH solution containing different concentrations of corrosion inhibitor. The test temperature of the corrosion solution was changed at 293K, 303K, 313K, and 323K to evaluate the corrosion and corrosion inhibition behavior.
[0048] 1.3 Electrochemical testing to study corrosion behavior
[0049] The electrochemical tests were performed on an electrochemical workstation equipped with a three-electrode system ( The CRS sheet was wrapped with epoxy resin, with an exposed surface area of 1cm×1cm. The surface was polished to a bright finish, cleaned with deionized water, and dried with cold air. It was designed as a working electrode. The platinum electrode was the auxiliary electrode, and the saturated calomel electrode was the reference electrode. The working electrode was immersed in a 0.1MCl3CCOOH solution containing different concentrations of BS-12 for 0.5h, and the test was performed after ensuring that the open circuit potential was stable. The electrochemical potentiodynamic polarization curve was tested in the range of -250 to 250mV, with a scan rate of 0.5mV·s -1The test frequency of electrochemical impedance spectroscopy (EIS) is 0.01~105Hz. p ) can be calculated by formula 3:
[0050]
[0051] Where: i corr(0) represents the corrosion current density of CRS in Cl3CCOOH solution without BS-12, i corr(inh) It represents the corrosion current density of CRS in Cl3CCOOH solution containing different concentrations of BS-12.
[0052] 1.4 Surface analysis
[0053] The surface functional groups of CRS were analyzed by attenuated total reflection infrared spectrometer (ATR-FTIR, ThermoFisher, USA); the surface morphology of CRS was observed by field emission scanning electron microscopy (SEM, FEI-Quanta250FE, USA), atomic force microscopy (AFM, Bruker, DimensionIcon, USA), and confocal laser scanning microscopy (CLSM, Leica-SP8SR, Germany); the surface properties of CRS in different corrosion solutions were observed by water contact angle meter (JC2000C1, Shanghai Zhongchen Digital Technology Equipment Co., Ltd., China); the surface elements of CRS were analyzed by X-ray photoelectron spectrometer (XPS, ThermoFisher, USA) to explore the mechanism of action in the corrosion inhibition process. All CRS samples were polished with sandpaper and cut into a size of 25mm×20mm, and then the samples were immersed in 0.1MCl3CCOOH solution containing different concentrations of BS-12 for 6h. Before the above tests, the CRS samples were washed with deionized water and dried in an oven.
[0054] 1.5 Theoretical calculation
[0055] Quantum chemical calculations were performed using MaterialsStudio7.0 software. The GGA / PBE / DNP method was used in the DMol3 module, and the density functional theory (DFT) was used to optimize the geometry of the BS-12 molecular structure. In addition, since the corrosion inhibitor was prepared in aqueous solution, water was designated as the solvent. A series of parameters were calculated and analyzed, including the highest occupied molecular orbital energy (E HOMO ), the lowest unoccupied molecular orbital energy (E LOMO ), energy gap (ΔE), Fukin index, etc.
[0056] The adsorption relationship between protonated BS-12 molecules and Fe(110) layers was simulated by MD. The simulated battery size is Contains 6 layers of Fe(110), 500 H2O molecules, 1 inhibitor molecule and Vacuum layer. Under periodic boundary constraints and COMPASS force field, the total time of high-precision simulation process is 1000ps, and the NVT ensemble time step used is 1fs. The interaction between Fe and inhibitor molecules satisfies the following formula, calculated Eq.4:
[0057] E Fe-inhibitor =E total -E Fe -E inhibitor (4)
[0058] Where: E total is the energy of the iron and adsorbed inhibitor molecules, E inhibitor is the energy of the inhibitor molecule, E Fe It is the energy of iron.
[0059] 1.6 Polyamide nanofiltration membrane performance test
[0060] Two commercially available nanofiltration membranes produced by Nanjing Weihua Membrane Technology Co., Ltd. were used to evaluate the effect of BS-12 on membrane performance. Sodium sulfate (Na2SO4) and magnesium chloride (MgCl2) were dissolved in deionized water to make 1 g·L -1 Feed liquid. Add 10 mg BS-12 to the feed liquid as the target system to evaluate the effect of BS-12 on membrane performance. The membrane performance is evaluated by membrane permeation (volume of permeate permeating the membrane per unit time and unit pressure) and retention rate (ability to separate solutes).
[0061] 2 Results and discussion
[0062] 2.1 Evaluation of corrosion inhibition behavior using weight loss method
[0063] Firstly, the corrosion behavior of CRS in 0.1 M trichloroacetic acid solution containing different concentrations of BS-12 was studied. Figure 1 As the concentration of BS-12 increases from 1 to 10 mg·L -1 Increase, the corrosion rate decreases ( Figure 1 The maximum corrosion inhibition efficiency can reach 95.3% in the middle b area. Comprehensive analysis shows that the addition of BS-12 can effectively inhibit the corrosion of CRS. In addition, this experiment simulates the CRS corrosion behavior of BS-12 at different temperatures. As the solution temperature increases from 293K to 323K, the corrosion inhibition efficiency decreases ( Figure 1The adsorption of BS-12 on the CRS surface was observed in the middle b area at high temperature. It was found that the BS-12 molecules were bonded to the CRS surface, which reduced the acid corrosion rate of the metal. Therefore, the corrosion kinetics and adsorption thermodynamic parameters were calculated to analyze the mechanism at 293K. Six adsorption isotherms were used to evaluate the adsorption thermodynamic behavior of BS-12 on the CRS surface ( Fig.10 ). It can be easily concluded that the adsorption thermodynamic behavior of BS-12 on the CRS surface at 293K is consistent with the EI-Awady isotherm ( Figure 1 The EI-Awady isotherm can be used to describe the adsorption behavior at 293 K, expressed by Equation 5:
[0064]
[0065] Where: C is the inhibitor concentration (mg·L -1 ); θ is the CRS surface coverage, which is approximately equal to the inhibition rate. y represents the number of inhibitor molecules on an active site, and y>1 indicates that the inhibitor is adsorbed in multiple layers on the active site. The slope value y<1( Figure 1 The c region in the middle indicates that BS-12 molecules are adsorbed in multiple layers on the surface, that is, BS-12 is physically adsorbed on the CRS surface. K is the adsorption equilibrium constant of the inhibitor on the CRS surface, which can be obtained by the intercept of the logarithmic function of θ / (1-θ) to C. Therefore, the standard adsorption Gibbs free energy of BS-12 on the CRS surface (ΔG θ ) can be calculated by Formula 6.
[0066]
[0067] Where: C solvent is the concentration of H2O in the solution. Since the test system is a very low concentration aqueous solution, its value is about 1.0×10 6 mg·L -1 . R is the gas constant (R = 8.314 J·(K·mol) -1 ), T is the thermodynamic temperature during the weight loss test.
[0068] BS-12 molecules can be adsorbed on the steel surface by absorbing or releasing energy. Standard adsorption enthalpy ΔH θ and standard adsorption entropy ΔS θ It can be calculated by formula 7-8:
[0069]
[0070] By calculation, it is found that 20<|ΔG θ|<40, indicating that the adsorption of BS-12 on the CRS surface is mixed adsorption (including physical adsorption and chemical adsorption). θ is negative, proving that the adsorption of BS-12 on the CRS surface is an exothermic reaction ( Figure 1 (c area in the middle). ΔS θ <0, indicating that the disorder of the system is reduced, which is not conducive to the reaction. This shows that the addition of BS-12 can prevent CRS from corroding in trichloroacetic acid solution. The corrosion kinetics of CRS in different solutions were further analyzed, and four corrosion kinetic parameters (lnA, E a , ΔH a , ΔS a ), expressed by formula 9-10.
[0071]
[0072] Where: A is the pre-exponential factor, E a is the apparent activation energy, ΔH a is the activation enthalpy, ΔS a is the activation entropy. N A is Avogadro's constant (6.022×10 23 ), h is Planck's constant (6.62×1034J·s).
[0073] Figure 1 The middle d region is the four corrosion kinetic parameters (lnA, E a , ΔH a , ΔS a ) change curve. It is worth noting that with the increase of BS-12 concentration, the activation energy (E a ) increases continuously, indicating that the adsorption of BS-12 molecules on CRS is mainly physical adsorption. The lower value indicates that the addition of lower BS-12 content is not enough to form a complete adsorption film to protect CRS from corrosion, and the corrosion reaction is easy to proceed. As the BS-12 concentration increases to 10 mg·L -1 , the adsorption amount of BS-12 molecules on the CRS surface increases and tends to form a thicker and more complete adsorption film, which effectively protects CRS from corrosion. Therefore, the activation energy (E a ) increases. The pre-exponential factor (A) indicates the effective collision frequency between reactants. After adding BS-12, the effective collision frequency between the corrosion inhibitor and the reactants increases, forming a more stable film layer, A increases, E a The changing trends of and A indicate that there is a significant inhibitory effect on the CRS corrosion process. Figure 1 The enthalpy change (ΔH a>0) indicates that the adsorption process of BS-12 is an endothermic process. The adsorption entropy change (ΔS a ) is always less than 0, indicating that the adsorption process reduces the disorder of the system and the adsorption process is orderly. With the increase of the concentration of the corrosion inhibitor, the adsorption layer becomes more ordered, resulting in entropy change. The corrosion inhibitor can form a more ordered and stable adsorption layer at a higher concentration, thereby enhancing its corrosion inhibition effect.
[0074] 2.2 Electrochemical testing
[0075] 2.2.1 Electrochemical test to evaluate corrosion inhibition behavior
[0076] The corrosion inhibition performance of CRS in Cl3CCOOH solution containing different concentrations of BS-12 at 293K was further observed using potentiodynamic polarization curves and electrochemical impedance spectroscopy (EIS). After adding BS-12, both the cathode and anode branches moved toward the direction of low corrosion current density ( Figure 2 It is worth noting that the shift of the anode potential is not obvious compared with that of the cathode, indicating that BS-12 is a mixed corrosion inhibitor that mainly affects the cathode reaction. The inhibitor can simultaneously inhibit the hydrogen evolution reaction at the cathode and the electrode dissolution at the anode. Figure 2 A series of parameters were obtained in the region a, and the results are listed in Table 1. corr The difference between the group with added corrosion inhibitor and the blank group did not change much (Table 1), indicating that BS-12, as a mixed corrosion inhibitor, mainly slowed down corrosion through the geometric coverage effect. corr This indicates that the BS-12 molecules initially adsorbed on the CRS surface make the charge transfer between the solution and the metal more difficult, thus achieving excellent corrosion inhibition efficiency (10 mg·L -1 The inhibition rate of BS-12 concentration was 90.6%. As the concentration of BS-12 increased, the cathode Tafel slope ( c ) decreased significantly, which is due to the formation of BS-12 adsorption layer that changes the cathode hydrogen evolution reaction mechanism. The anode Tafel zone is not obvious, and reliable Tafel parameters cannot be extracted, but the shape of the anode PDP curve remains unchanged, indicating that the addition of BS-12 will not change the anode corrosion mechanism. Considering the complex corrosion inhibition process between metal and corrosion inhibitor, the anode reaction index (f a ) and the cathode reaction index (f c ) to study the corrosion inhibition mechanism. a or c <1, indicating that the corrosion inhibitor binds to the active sites on the metal surface, thereby preventing the corrosion reaction. c It can be calculated by formula 11:
[0077]
[0078] f in Table 1 c The values indicate that the adsorption of BS-12 on the CRS surface is gradually enhanced, which effectively alleviates the corrosion of electrolyte ions.
[0079] Table 1 Fitting electrochemical corrosion parameters of CRS after immersion in different solutions
[0080]
[0081] Electrochemical impedance spectroscopy can obtain the kinetic information of reactive corrosion at the interface between metal and solution. After CRS was immersed in Cl3CCOOH solution containing different concentrations of BS-12, the electrochemical impedance of CRS was tested. CRS immersed in pure Cl3CCOOH solution showed an induction arc in the low-frequency region, which was caused by the equivalent inductance (R L ), that is, a loose and homogeneous surface is formed in the corrosive solution ( Figure 2 The impedance arcs all present irregular semicircular curves, which are caused by the heterogeneous adsorption (diffusion effect) of BS-12 on the surface of CRS. The diameter of the impedance arc curve increases with the increase of BS-12 concentration, indicating that the corrosion inhibition efficiency of BS-12 on CRS is improved. In addition, similar arcs indicate that the corrosion mechanism of CRS does not change after being immersed in solutions containing different BS-12 concentrations. In addition, the electrochemical impedance spectroscopy (EIS) of cold rolled steel (CRS) immersed in trichloroacetic acid (TCA) medium for different time periods was also tested ( Fig.11 ). use( Fig.11 ) was fitted to the time gradient parameters using the fitting circuit. It was found that as time increased from 0.5h to 4h, the capacitance arc radius first increased and then remained unchanged. This indicates that BS-12 molecules can form a stable adsorption layer on the CRS surface, thereby playing a relatively long-lasting corrosion inhibition role. It is worth noting that as time increases, EIS gradually changes to fitting R(QR)(QR). This is because as time goes on, the thickness of the adsorption film formed by the corrosion inhibitor molecules on the CRS surface continues to increase, which in turn leads to the film resistance (R f ) increased. However, from the EIS point of view, the charge transfer resistance still plays a dominant role. This further confirms that BS-12 has stable corrosion inhibition performance. The impedance modulus can reflect the penetration corrosion process. The higher the impedance modulus value, the more difficult the penetration process of ions in the solution, and the better the corrosion inhibition effect. The impedance modulus value is much higher than the impedance modulus value of CRS in pure Cl3CCOOH solution, proving that the addition of BS-12 can inhibit the corrosion of CRS ( Figure 2The phase angle shifts to the positive direction, proving that a higher BS-12 concentration is conducive to the adsorption of BS-12 on the CRS surface. Therefore, CRS exhibits a good corrosion inhibition effect in the corrosive Cl3CCOOH solution containing different concentrations of BS-12. Further, two circuits ( Figure 2 The impedance of the middle d area is calculated by ZSimDemo software. s and R p Represent solution resistance and polarization resistance respectively. L is the inductor resistance, CPE is the constant phase angle component, C dl is the interface double layer capacitance, n is the dispersion coefficient, and L is the inductance value. dl It can be calculated by formula 12:
[0082] C dl =CPE×(2πf max ) n-1 (12)
[0083] In the formula, f max is the maximum frequency corresponding to the maximum impedance of the Nyquist diagram, and the EIS suppression rate η R It can be calculated by formula 13:
[0084]
[0085] C dl It decreases with the increase of inhibitor concentration. It can be calculated according to the Helmholtz double layer capacitance model by formula 14:
[0086]
[0087] In the formula, ε 0 is the vacuum dielectric constant, ε is the electrolyte dielectric constant, d is the film thickness, and S is the electrode surface area. The circuit model (I) was used to calculate the CRS of the blank 0.1 MCl3CCOOH solution, and the circuit model (II) was used to calculate the CRS of the solutions containing BS-12 (1 mg·L -1 , 5mg·L -1 、10mg·L -1 The CRS of 0.1 M Cl3 CCOOH solution is shown in Table 2. 2 The value is small enough, which proves that the two circuit diagrams fit the system well. Solution resistance (R s ) is attributed to the partial ionization of Cl3CCOOH in aqueous solution. After adding BS-12, R s The metal / solution interface resistance is complex and variable, including charge transfer resistance (R ct ), diffusion resistance (Rd )、film resistance (R f ) and the accumulation resistance (R a Therefore, a comprehensive analysis of the suppression performance of BS-12 was conducted, and the polarization resistance (R P is the sum of various resistances). Table 2 shows that with the addition of corrosion inhibitor, R P The increase in the charge transfer resistance was significant, indicating that the charge transfer resistance was effectively controlled, thereby reducing the degree of corrosion. -1 When the corrosion inhibition rate reaches 95.4%, the EIS parameters (C dl ) decreased significantly, which is due to the fact that the corrosion inhibitor molecules are adsorbed on the CRS / solution interface, replacing water molecules with a large dielectric constant or increasing the thickness of the double layer.
[0088] Table 2 Fitting parameters of two equivalent circuits of CRS after immersion in BS-12 solutions of different concentrations
[0089]
[0090] 2.3 Effect of BS-12 on the morphology and surface properties of CRS after corrosion
[0091] The weight loss method and electrochemical analysis showed that the addition of BS-12 can effectively improve the corrosion inhibition performance of CRS in trichloroacetic acid solution. Therefore, a series of characterization methods (FE-SEM, AFM and CLSM) were used to observe the corrosion of CRS in the presence of 10 mg·L -1 Changes in the surface morphology of CRS after immersion in trichloroacetic acid solution of BS-12 for 6 h ( Figure 3 ). The polished CRS surface has clear scratches ( Figure 3 After CRS was immersed in Cl3CCOOH, a large amount of corrosion products appeared on the surface of CRS ( Figure 3 After adding BS-12 to Cl3CCOOH, clear scratches appeared on CRS ( Figure 3 AFM ( Figure 3 b1-b3 area) and CLSM ( Figure 3c1-c3 region) The results show that the surface of CRS after corrosion becomes rougher compared with the polished CRS sample, while the addition of BS-12 can keep the surface of CRS smooth. A series of characterizations prove that the addition of BS-12 can effectively prevent the corrosion of CRS in trichloroacetic acid solution. In addition, compared with the polished CRS surface (71.22°), the WCA of the corroded CRS surface is reduced to 55.87°, while the WCA of CRS with the addition of BS-12 in Cl3CCOOH increases to (105.64°). Both hydrophilic and rough surfaces can lead to lower WCA, while hydrophobic and smooth surfaces can lead to higher WCA. Therefore, it can be concluded that the decrease in WCA (55.87°) is due to the surface roughness, while the increase in WCA (105.64°) is due to the hydrophobic surface of CRS formed by the adsorption of BS-12.
[0092] Therefore, ATR-FTIR and XPS spectroscopy were further used to observe the changes in surface chemical composition properties ( Figure 4 ). After CRS was immersed in Cl3CCOOH solution for 6 hours, almost no obvious organic peaks were observed on the surface of CRS. After BS-12 was added to the Cl3CCOOH solution, the surface of CRS showed a spectrum similar to that of pure BS-12. This indicates that BS-12 was successfully adsorbed on the surface of CRS. Therefore, XPS was used to analyze the surface chemical composition of CRS samples immersed in Cl3CCOOH solution containing BS-12 for 6 hours. CRS was immersed in a solution containing 10 mg·L -1 After 6 hours in the trichloroacetic acid solution of BS-12, Fe2p, O1s, N1s and C1s were detected, proving that BS-12 was successfully adsorbed on the CRS surface. No peak belonging to Cl appeared, indicating that the BS-12 adsorption layer had an inhibitory effect on the attack of Cl3CCOOH molecules on the CRS surface. In order to further analyze the main existence form of the elements, the elements were deconvoluted ( Figure 4 cf region), the peak at 706.7 eV is attributed to Fe 0 The satellite peak at 719.42 eV is due to the undissolved Fe 3+ (Fe2O3) and Fe 0 The peak at 724.05eV (Fe2p1 / 2) and the satellite peak at 719.42eV prove the formation of Fe3O4. The peak at 711eV indicates the presence of FeOOH. Therefore, further deconvolution of O1s confirmed the presence of FeOOH and Fe3O4. In addition, C1s ( Figure 4 The results in the middle e area prove that BS-12 is successfully adsorbed on the CRS surface. Figure 4 The middle (f) region indicates that BS-12 reacted with the CRS surface during the adsorption process.
[0093] 2.4 Theoretical calculation
[0094] 2.4.1 Quantum chemical analysis
[0095] In order to further explore the mechanism of BS-12's corrosion inhibition on CRS, quantum chemical calculations were used to analyze the corrosion inhibition process. First, the chemical structure of BS-12 was optimized using Materialsstudio software based on density functional theory (DFT) to achieve the minimum energy ( Figure 5 The nucleophilicity and electrophilicity of BS-12 structure were analyzed using electrostatic potential surface analysis ( Figure 5 The blue color represents the negative charge property, indicating that the part tends to donate electrons. The red color represents the positive charge property, indicating that the part tends to accept electrons. Therefore, it can be concluded that during the adsorption process, O and N donate electrons to CRS. According to the frontier molecular orbital theory, E HOMO (-4.319eV) represents the ability of the molecule to donate electrons, indicating that the stronger the ability to bind to the empty metal orbital ( Figure 5 middle a area). E LUMO (0.013eV) represents the ability of the molecule to accept electrons ( Figure 5 (b area in the middle). HOMO and E LOMO The value of E indicates that BS-12 tends to donate electrons to CRS during adsorption. HOMO With E LOMO Subtracting ΔE from each other indicates the reactivity of the molecule. The lower the ΔE value, the higher the chemical reactivity of the molecule, and thus the better the stable adsorption capacity and corrosion inhibition efficiency of the molecule on the CRS surface. In addition, the Fukin parameter ( Figure 5 The active sites in the adsorption process were analyzed by using the c and d regions in the middle. According to the results of f(r→)^+ and f(r→)^-, the electrophilic and nucleophilic centers are mainly distributed in the carboxyl part. In addition, the Mulliken charge of the corrosion inhibitor was further measured ( Figure 5 e region) to accurately evaluate the surface adsorption structure of corrosion inhibitors and CRS. Figure 5 The middle e region clearly shows the positive and negative charge distribution of BS-12 atoms. Atoms are almost always negatively charged. CRS is positively charged in acidic solution, so BS-12 can interact with the CRS surface through electrostatic attraction.
[0096] 2.4.2 Molecular dynamics simulation
[0097] The adsorption behavior of BS-12 on the CRS surface was observed using molecular dynamics simulation. The position of BS-12 molecules gradually changed from vertical to horizontal ( Figure 6The flat morphology of the molecule is conducive to the formation of an adsorption layer to protect the corrosive ions (H + , Cl - ) does not directly contact the CRS surface. In addition, the hydrophobic carboxyl part can inhibit the contact between H2O and the CRS surface and also reduce the corrosion of CRS. The binding energy of BS-12 and H2O on the CRS surface was calculated respectively. The binding energy of BS-12 on CRS (-233.69KJ·mo l-1 ) is lower than the binding energy of H2O (-21.67KJ·mol -1 ), indicating that BS-12 is preferentially adsorbed on the CRS surface than H2O. In addition, the radial distribution function between BS-12 and the CRS surface was calculated, and the peak appears at The following indicates that chemical adsorption exists, otherwise it is physical adsorption. It is inferred that chemical adsorption and physical adsorption occur between Fe-C=O and Fe-O ( Figure 6 d and e regions), while physical adsorption was formed between Fe and N ( Figure 6 middle f area).
[0098] 2.4.3 Projected state density
[0099] XPS results and molecular dynamics simulations prove that chemical adsorption and physical adsorption occur simultaneously during the adsorption of BS-12 on the CRS surface, but the electron exchange information is not considered, which is not convincing. Therefore, the density of states is further simulated to observe the electron exchange between BS-12 and the Fe(110) surface, and the adsorption performance of the corrosion inhibitor molecule on the metal surface is systematically discussed. Figure 7 In the middle a region, it can be clearly seen that there is electron exchange between the heteroatoms (N and O) and the Fe (110) plane ( Figure 7 b area), indicating that there is a strong interaction between BS-12 and Fe(110), and the adsorption energy is Eads = -352.36 kJ·mol -1 The projected density of states (PDOS) before and after adsorption was calculated ( Figure 7 The adsorbed N and O heteroatoms and P orbitals overlapped with the Fe d orbitals over a large area, indicating that the inhibitor molecules interacted strongly with the Fe (110) surface. The p orbital curves of N and O changed, and the energy of the Fe d orbital increased, indicating that BS-12 donated electrons to the Fe d orbital, which is consistent with the previous experimental results, that is, BS-12 was chemically adsorbed on the CRS surface.
[0100] Evaluation of the effect of 2.5BS-12 addition on the performance of polyamide nanofiltration membrane
[0101] In order to evaluate the effect of adding Bs-12 as an inhibitor on membrane performance, the stability of membrane performance was tested. Two typical thin film composite membranes with opposite surface charges were used, respectively, with 10 mg·L -1 BS-12 Na2SO4 and MgSO4 solution (1g·L -1 ) as the feed solution. After 24 hours of testing, the membrane permeability and retention rate of the solute ( Figure 8 ) remained stable. Therefore, it can be concluded that the addition of BS-12 as an inhibitor does not affect the membrane performance. BS-12 shows good potential in the application of CRS corrosion inhibition in membrane treatment.
[0102] 2.6 Corrosion inhibition mechanism
[0103] Based on a series of experiments and theoretical analysis, the corrosion and inhibition mechanisms were speculated ( Fig. 9 ). In the three-electrode system, the corrosion reaction of CRS under Cl3CCOOH treatment includes hydrogen evolution (cathode) and electrolysis (anode). The overall reaction is as follows:
[0104] Fe+Cl3CCOOH→FeCl2+Cl2CCOOH+H2
[0105] Cl3CCOOH will ionize into Cl3CCOO- and H+. The CRS surface is positively charged. Negatively charged Cl3CCOO- is adsorbed on the CRS surface and forms a double electrical layer. The resulting anode reaction is as follows:
[0106] Fe+Cl3CCOO - →(FeCl3CCOO-) ads
[0107] (FeCl3CCOO - ) ads →(FeCl3CCOO) ads +e -
[0108] (FeCl3CCOO) ads →(FeCl3CCOO+)+e -
[0109] (FeCl3CCOO + )→Fe 2+ +Cl3CCOO -
[0110] Cl3CCOO - After being adsorbed on the CRS surface, H + Move to the CRS surface, generate H2 on the CRS surface, and the continuous reaction is as follows:
[0111] Fe+H + →(FeH + ) ads
[0112] (FeH + ) ads +e - →(FeH) ads
[0113] (FeH) ads +H + +e - →Fe+H2
[0114] Results The CRS surface was severely corroded, the surface was rough, and there were corrosion products ( Fig. 9 After BS-12 was added to the Cl3CCOOH solution, the corrosion process of CRS was inhibited and the surface became smooth ( Fig. 9 BS-12 is more likely to behave as a cationic surfactant in acidic solution. First, BS-12 is adsorbed on the Cl3CCOO on the surface of CRS under the control of electrostatic interaction. - In addition, Fe in CRS has an empty orbital, and the lone pair of electrons of O in BS-12 can form a coordination bond with the empty orbital of Fe. Therefore, BS-12 can form a complete adsorption layer through physical adsorption and chemical adsorption, thereby improving the corrosion inhibition efficiency of CRS in Cl3CCOOH solution. Compared with many literatures on corrosion inhibitors in trichloroacetic acid solution, this further proves the outstanding advantages of BS-12 as a corrosion inhibitor ( Fig.12 ).
[0115] in conclusion
[0116] In view of the corrosion inhibition requirements of CRS in membrane separation and purification processes, the present invention designs an amphoteric surfactant, dodecyl dimethyl betaine (BS-12), as a corrosion inhibitor to improve the corrosion inhibition efficiency of CRS in a trichloroacetic acid (TCA) system. The research results are as follows:
[0117] (1) Weight loss method proves that trace (10 mg·L -1 )'s BS-12 showed good corrosion inhibition effect (95.3%) through chemical adsorption and physical adsorption.
[0118] (2) Electrochemical tests show that the addition of BS-12 increases the anodic and cathodic corrosion inhibition efficiencies of CRS to 90.6% at the same time. A series of characterization results show that the addition of BS-12 can stabilize the CRS surface and prevent corrosion through physical and chemical adsorption.
[0119] (3) Molecular dynamics simulations show that BS-12 inhibits the movement of corrosive ions to the surface of CRS by surface adsorption, showing a good corrosion inhibition effect. Density of state analysis proves that the electrons in the p orbital of heteroatoms (N and O) are transferred to the d orbital of Fe (110), indicating that the strong interaction between BS-12 and CRS makes CRS show a good corrosion inhibition effect in trichloroacetic acid (TCA).
[0120] (4) The long-term stability test of the membrane showed that the addition of BS-12 did not have any adverse effects on the membrane performance. BS-12 showed great potential in CRS corrosion inhibition in membrane separation and purification processes. This study can provide a useful reference for the corrosion control of CRS in seawater softening membrane devices.
[0121] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A method for slowing down the corrosion of cold-rolled steel using a biodegradable surfactant, characterized in that: The method comprises adding a biodegradable surfactant to a solution system having cold-rolled steel; wherein, The biodegradable surfactant is dodecyl dimethyl betaine, and the concentration in the solution system is 0.5-15 mg·L -1 ; The concentration of the corrosive medium in the solution system is 0.05-2 mol·L -1 .
2. The method for slowing down cold-rolled steel corrosion using a biodegradable surfactant according to claim 1, characterized in that: The temperature of the solution system with cold rolled steel is 200-400K.
3. The method for slowing down cold-rolled steel corrosion using a biodegradable surfactant according to claim 1, characterized in that: The corrosive medium is trichloroacetic acid.
4. The use of biodegradable surfactants as corrosion inhibitors for cold rolled steel in membrane separation processes, characterized in that: The biodegradable surfactant is added to the feed liquid and passed through a membrane separation system having cold-rolled steel; The biodegradable surfactant is dodecyl dimethyl betaine, and its concentration in the feed liquid is 0.5-15 mg·L -1 .
5. The use according to claim 4, characterized in that: The membrane used in the membrane separation system is a negatively or positively charged membrane.
6. The use according to claim 4, characterized in that: The membrane used in the membrane separation system is a nanofiltration membrane.
7. The use according to claim 4, characterized in that: The membrane used in the membrane separation system is used to separate Na2SO4 or MgSO4 in the feed liquid.
8. A method for predicting the adsorption type of surfactant on the surface of cold-rolled steel, characterized in that: The molecular structure of the surfactant includes a glycine group, and an alkyl group containing 8 to 16 carbon atoms is connected to the nitrogen atom; The method comprises the following steps: The radial distribution function between the surfactant and the cold-rolled steel surface was calculated by molecular dynamics simulation. If the peak appears If the value is below , it is chemical adsorption, otherwise it is physical adsorption; Alternatively, by calculating the projected density of states before and after the surfactant is adsorbed on the Fe(110) surface, if the adsorbed N, O heteroatoms and P orbitals overlap with the Fe d orbital, and the N and O p orbital curves change, the Fe d orbital energy increases, indicating that the surfactant donated electrons to the Fe d orbital and chemical adsorption occurred.